Evaluation of expanded peripheral blood derived CD34+ cells for the treatment of moderate knee osteoarthritis - Vignon, Christine; Hilpert, Morgane; Toupet, Karine; Goubaud, Aurélien; Noël, Danièle; de Kalbermatten, Matthieu; Hénon, Philippe; Jorgensen, Christian; Barbero, Andrea; Garitaonandia, Ibon (Frontiers in Bioengineering and Biotechnology, 2023)
Knee osteoarthritis (OA) is a degenerative joint disease of the knee that results from the progressive loss of articular cartilage. It is most common in the elderly and affects millions of people worldwide, leading to a continuous increase in the number of total knee replacement surgeries. These surgeries improve the patient's physical mobility, but can lead to late infection, loosening of the prosthesis, and persistent pain. We would like to investigate if cell-based therapies can avoid or delay such surgeries in patients with moderate OA by injecting expanded autologous peripheral blood derived CD34+ cells (ProtheraCytes®) into the articular joint. Here we show that ProtheraCytes® maintain high viability (>95%) when exposed for up to 96 hours to synovial fluid from OA patients. Additionally, when co-cultured with OA chondrocytes, ProtheraCytes® can modulate the expression of some chondrogenic (collagen II and Sox9) and inflammatory/degrading (IL1β, TNF, and MMP-13) markers at gene or protein levels. Finally, ProtheraCytes® survive after injection into the knee of a collagenase-induced osteoarthritis mouse model, engrafting mainly in the synovial membrane, probably due to the fact that ProtheraCytes® express CD44, a receptor of hyaluronic acid, which is abundantly present in the synovial membrane. This report provides preliminary evidence of the therapeutic potential of CD34+ cells on OA chondrocytes in vitro and their survival after in vivo implantation in the knee of mice and merits further investigation in future preclinical studies in OA preclinical models.